A snapshot of membrane protein insertion. (13th September 2019) - Tanaka, Yoshiki; Tsukazaki, Tomoya
Abstract : The cytoplasm is the main place for protein translation from where nascent proteins are transported to their working areas, including the inside, outside, and membrane of the cell. The majority of newly synthesized membrane proteins is co‐translationally inserted into the membrane by the evolutionary conserved Sec translocon. In this issue of EMBO Reports, Kater et al [1] use single‐particle cryo‐electron microscopy to visualize a high‐resolution structure of the E. coli SecYEG translocon:ribosome‐nascent chain complex in a lipid environment constituted by nanodiscs. This snapshot represents an early intermediate state in membrane protein insertion and provides important information for understanding the molecular mechanism of membrane protein biogenesis. Abstract : The SecYEG translocon provides the major route for co‐translational membrane protein insertion in bacteria. A cryo‐electron microscopy structure of SecYEG in lipid nanodiscs bound to a translating ribosome reveals an intermediate stage of protein insertion.